Lightweight noncommutative key exchange protocol for IoT environments - Kanwal, Shamsa; Inam, Saba; Ali, Rashid; Cheikhrouhou, Omar; Koubaa, Anis (Frontiers in Environmental Science, 2022)
Network communications are expanding quickly in many fields, including telecommunications, the Internet of Things, space, consumer electronics, and the military. Different privacy and security issues are present in these areas. The Internet of Things (IoT) has drawn increased attention from academic and industrial researchers during the last few decades. Keys are routinely exchanged using a public key exchange protocol to support the highly secured IoT domain and thwart security threats from unauthorized parties. The environment for IoT devices is subject to numerous limitations, including those relating to processing, memory, and energy. They need to pass via a gateway or sink to connect to the network. Additionally, the IoT environment must enable secure communication between gateways and IoT devices even in their disconnected mode from the rest of the network. In this paper, a lightweight key exchange protocol for IoT environments is presented, allowing the gateway and IoT device to communicate over an open channel. Our protocol is based on polynomials over noncommutative rings. The underlying idea is the generalized decomposition problem over noncommutative rings. It is demonstrated that the proposed protocol improves security by utilizing noncommutative structures and polynomials over noncommutative rings. Furthermore, it is discussed how the suggested protocol can achieve key certification and perfect forward secrecy. As a result, this protocol is a strong candidate for key sharing and secure communication between (IoT) devices. We put our methodology into practice and the results of our experiments demonstrate that the security level has enhanced. The performance analysis of the suggested work is compared with some protocols in terms of security, communication, and computing overhead.